2020
DOI: 10.2174/1389202921666200102163422
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation and Bladder Cancer: Where Genotype does not Predict Phenotype

Abstract: Nearly three decades ago, the association between Bladder cancer (BC) and DNA methylation has initially been reported. Indeed, in the recent years, the mechanism connecting these two has gained deeper insights. Still, the mediocre performance of DNA methylation markers in the clinics raises the major concern. Strikingly, whether it is the inter-individual methylation variations or the paucity of knowledge about methylation fingerprints lying within histologically distinct subtypes of BC requires critical discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…Four cell lines: K562 (leukemia), Raji (lymphoma), SU-DHL-4 (lymphoma) (all from DSMZ, Braunschweig, Germany), and mouse mastocytoma P815 (ATCC) were primarily used in this study. Of note, as discussed previously, the heterogeneity between cancer cell lines (in addition to geneticepigenetic variations) and inter-individual differences can lead to experimental discrepancies (29); in our study, with four stable cell lines and four donors, no inconsistencies were observed. Concerning antibodies (Abs) and cytokines, anti-CD3 (OKT3) and anti-2B4 (C1.7) were purchased from eBioscience (Inc. San Diego, CA, U.S.A.).…”
Section: Cell Culture and Antibodiessupporting
confidence: 49%
“…Four cell lines: K562 (leukemia), Raji (lymphoma), SU-DHL-4 (lymphoma) (all from DSMZ, Braunschweig, Germany), and mouse mastocytoma P815 (ATCC) were primarily used in this study. Of note, as discussed previously, the heterogeneity between cancer cell lines (in addition to geneticepigenetic variations) and inter-individual differences can lead to experimental discrepancies (29); in our study, with four stable cell lines and four donors, no inconsistencies were observed. Concerning antibodies (Abs) and cytokines, anti-CD3 (OKT3) and anti-2B4 (C1.7) were purchased from eBioscience (Inc. San Diego, CA, U.S.A.).…”
Section: Cell Culture and Antibodiessupporting
confidence: 49%
“…In our current analysis, both cell lines showed very low levels of PD-L1 and PD-L2, however, a significant increase in PD-L1 (but not PD-L2) was observed when CIK cells were co-cultured with them. To mention, the PD-L1/L2 levels may vary in other B-NHL cell lines (>100 reported in ATCC repositories), as suggested by Sharma et al the heterogeneity between cancer cell lines (in addition to genetic-epigenetic variations) may lead to discrepancies in the experimental data ( 17 ). In our study we could show that the variation in cell viability was entirely due to co-cultured CIK cells, thus the above-mentioned factor can be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, one independent study described four-immune-related-LncRNA signatures for predicting the prognosis and guiding the application of immunotherapy in HCC [ 33 ]. However, it is worth mentioning that the heterogeneity within clinical samples submitted to repositories (as previously described by Sharma et al [ 34 ]) and especially the selection of different computational analytical methods makes these predictive markers less effective in the clinical environment. In the present study, we have provided a detailed description of the methods used in our analysis, which offers a platform for methodological compression to enable similar analyses in HCC or in other cancers.…”
Section: Discussionmentioning
confidence: 99%